Peran Manejemen Strategi Guna Evaluasi Pasca Akreditasi pada Klinik Pratama : Literature Review - Denna Idryareza Augustyana; Rizky Perdana Putra; Purwadhi Purwadhi; Yani Restiani Widjaja (Syntax Corporation Indonesia, 2024)
Strategic management has a very important consideration and must be reviewed as part of the evaluation of the accreditation process in FKTP (First Level Health Facilities). A well-formulated strategy must be skillfully implemented to ensure growth and progress. This strategy needs to be implemented by every FKTP staff member to improve service quality, evaluation, and accreditation status. The purpose of this theoretical research article is to understand and push back to the theoretical field of various literary works. One of the methods used is theoretical research by analyzing and comparing existing theories. The results of this theoretical study show how strategic management functions in evaluation and helps FKTP make better plans with a more logical, rational, and systematic approach to each choice found during the planning process. It is clear that to improve the quality of health services, strategic management is also needed. The focus of FKTP accreditation strategic management is the assessment and determination of the hospital's eligibility according to service standards that have been set by an independent accreditation institution. So that it can improve patient perceptions and their trust in health facilities. After accreditation, FKTP must carry out strategic management optimally. Thus, the organization improves infrastructure, adequate human resources, and supporting facilities.